2023
DOI: 10.1186/s12885-023-10677-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analyzes identify CCT3 as a modulator to shape immunosuppressive tumor microenvironment in lung adenocarcinoma

Abstract: Background Chaperonin-containing tailless complex polypeptide 1 (TCP1) subunit 3 (CCT3) has tumor-promoting effects in lung adenocarcinoma (LUAD). This study aims to investigate the molecular mechanisms of CCT3 in LUAD oncogenesis. Methods The UALCAN databases, Human Protein Atlas (HPA) and The Cancer Genome Atlas (TCGA) data were used to analyze CCT3 expression in LUAD. Both the Wilcoxon rank-sum test and the regression model were used to investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The ESTIMATEScore represents the purity of the tumor, and in one study, it was found that a low purity of the tumor indicates an advanced stage and poor prognosis of the tumor [40] . In a previous study, CCT subunits were found to be associated with TME [23] , and in the results of pathway enrichment analysis, each subunit of CCT was mostly enriched in immune-related pathways. Therefore, in this study, we rst analyzed the expression of each subunit of CCT by correlating it with the immune in ltration of the stromalscore, immuneScore, and ESTIMATEScore.…”
Section: Discussionmentioning
confidence: 81%
“…The ESTIMATEScore represents the purity of the tumor, and in one study, it was found that a low purity of the tumor indicates an advanced stage and poor prognosis of the tumor [40] . In a previous study, CCT subunits were found to be associated with TME [23] , and in the results of pathway enrichment analysis, each subunit of CCT was mostly enriched in immune-related pathways. Therefore, in this study, we rst analyzed the expression of each subunit of CCT by correlating it with the immune in ltration of the stromalscore, immuneScore, and ESTIMATEScore.…”
Section: Discussionmentioning
confidence: 81%